Ocenění společnosti Strojírny Poldi, a.s. - Rožnovská, Jana; Mařík, Miloš, 1947-; Jalový, Milan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2010)
The main aim of the thesis is appoint the value of firm Strojírny Poldi, a.s. on 1st January 2009. Short history and basic profile of the firm are introduced at the beginning. Second part follows strategic analysis. The output of this part is two variations of the revenue forecast. Third chapter contains financial analysis, which is followed by the fourth one - the prognosis of value creator and construction of two variations of financial plan. Last chapter is the final valuation. DCF Equity was applied as the main valuation method and the value of the firm is appointed like an interval. The alternative valuation method is the method of Market comparison.
Vedoucí práce: Miloš Mařík
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2010
Rok obhajoby 2010
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses